Use of psychoactive substances by students of a rural school: distribution by sex and age - Mônica Cecília Pimentel de Melo; Ana Karla da Silva Freire; Bruno Passos Sampaio; Filipe Pitágoras Rodrigues Magalhães; Marianna Fernandes Miranda; Maria de Fátima Alves Aguiar Carvalho; Deisiluce Miron Cavalcante (Universidade Federal de Santa Maria, 2015)
Doi: 10.5902/2179769214144 Objective: to analyze the lifetime use of alcohol, tobacco and other drugs, and their distribution by sex and age of students of elementary and high school, in a rural public school. Method: quantitative, descriptive and cross-sectional study, conducted from August to November of 2011 with 146 students in Petrolina and analyzed by Microsoft Excel 2007. As for the criteria of eligibility, elligible students had to be over 18 and sign the Informed Consent or, if underage, obtain the parents' signature. Results: there was greater lifetime use of alcohol, predominantly among women of 16-18 years old; 16.44% used cigarettes, without distinction of sex; and 3.42% used illicit drugs, prevailing men. Conclusions: educational strategies, through school, family or government, are necessary to promote dialogues with students, reducing the use of alcohol, tobacco and other drugs among students.